2019
DOI: 10.18203/2320-1770.ijrcog20191235
|View full text |Cite
|
Sign up to set email alerts
|

Indication and complication of caesarean section at tertiary care hospital: a retrospective study

Abstract: Background: The incidence of cesarean section is steadily rising. Cesarean delivery has played a major role in lowering both maternal and perinatal morbidity and mortality rates.  There are various factors involved in the rise of rate of cesarean section like rising incidence of primary cesarean delivery, identification of high-risk pregnancy, wider use of repeat cesarean section, rising rates of induction of labor and failure of induction, no reassuring fetal status etc.Methods: A retrospective cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…These results are similar to those of a recent study, in which 63.6% of cases were emergency CSs and only 36.4% of cases were planned CSs [10].…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…These results are similar to those of a recent study, in which 63.6% of cases were emergency CSs and only 36.4% of cases were planned CSs [10].…”
Section: Resultssupporting
confidence: 91%
“…The proportion of women aged 21-30 years was similar in both study groups (48.0% and 58.3%, respectively; p > 0.05). Rehman et al, in a recent study, confirmed that most women who underwent CS were aged 21-30 years (67.1%) [10].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations